Deeply rooted glaciotectonism in western Denmark: geological composition, structural characteristics and the origin of Varde hill‐island - A.‐S. HØYER; F. JØRGENSEN; J. A. PIOTROWSKI; P. R. JAKOBSEN (Journal of Quaternary Science, 2013)
We investigate a hill‐island in western Denmark, a major cupola‐hill‐type thrust complex generated by ice‐marginal glaciotectonism. The study uses a unique dataset of densely spaced airborne electromagnetic data, high‐resolution seismic data and borehole information to document the complexity of deeply rooted thrust sheets comprising Miocene to middle Pleistocene deposits. The deformation spans at least 150 m of sediment thickness, placing this complex among the largest glaciotectonic features on record. The main stages of formation of the hill‐island were (1) erosion of Miocene deposits by subglacial tunnel valleys and infill of these valleys in the pre‐Elsterian and Elsterian time, (2) two phases of glaciotectonic thrusting during the Saalian glaciation, (3) erosion by the Saalian ice sheet removing a significant part of the thrust complex and (4) periglacial and postglacial erosion of the hill‐island excavating the glaciotectonic elements. Palaeoglaciological calculations suggest that the Saalian ice sheet that caused the thrusting was thick, had a steep profile, rested on a permafrost wedge and moved slowly, which contrasts with the highly mobile, thin ice lobes of the Last Glaciation.